login
A076899
Let u(1)=u(2)=u(3)=1, u(n)=sign(u(n-1)-u(n-2))/(u(n-3)+1); then a(n) is the denominator of u(n).
1
1, 1, 1, 1, 2, 2, 1, 1, 1, 1, 3, 3, 1, 2, 2, 1, 5, 5, 1, 3, 3, 1, 8, 8, 1, 5, 5, 1, 13, 13, 1, 8, 8, 1, 21, 21, 1, 13, 13, 1, 34, 34, 1, 21, 21, 1, 55, 55, 1, 34, 34, 1, 89, 89, 1, 55, 55, 1, 144, 144, 1, 89, 89, 1, 233, 233, 1, 144, 144, 1, 377, 377, 1, 233, 233, 1, 610, 610, 1, 377
OFFSET
1,5
FORMULA
F(k) denotes the k-th Fibonacci number: a(6k)=F(k+2); a(6k+1)=1; a(6k+2)=a(6k+3)=F(k+1); a(6k+4)=1; a(6k+5)=F(k+3).
Empirical g.f.: -x*(x^14+x^13+x^12-x^11-x^10+2*x^8+2*x^7+x^6-x^5-x^4-x^2-x-1) / ((x-1)*(x^2+x+1)*(x^12+x^6-1)). - Colin Barker, Oct 14 2014
CROSSREFS
Cf. A076898 (numerators).
Sequence in context: A206474 A211999 A175025 * A152905 A096601 A078077
KEYWORD
frac,nonn
AUTHOR
Benoit Cloitre, Nov 26 2002
STATUS
approved